The Influence of Unemployment and Regional Income on Community Purchasing Power in Pidie Jaya Regency - Akmaluddin Akmaluddin; M. Rasyidin; M. Saleh (SAINTIS Publishing, 2025)
This research is motivated by the low purchasing power of the community in Pidie Jaya Regency, which is suspected to be influenced by high unemployment rates and income fluctuations. The aim of this study is to analyze the effect of unemployment and income levels on purchasing power during the period 1994–2023. The method used is a quantitative approach with multiple linear regression analysis, utilizing secondary data obtained from the Central Bureau of Statistics and related institutions. The results indicate that the unemployment rate variable (X₁) has a negative and significant effect on purchasing power (Y), while the income variable (X₂) has a positive and significant effect. These findings suggest that higher unemployment rates tend to reduce purchasing power, whereas increased income can enhance it. This highlights the need for local government policies to focus on job creation and income improvement to strengthen purchasing power and promote economic welfare in Pidie Jaya. The study is expected to serve as a reference for formulating more effective and sustainable regional economic development strategies.